2011
DOI: 10.1007/s12098-011-0364-6
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Activated Factor VII Usage in Life Threatening Hemorrhage: A Pediatric Experience

Abstract: rFVIIa appears to be safe and effective in controlling life-threatening bleed in non-hemophiliac children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…Overall, 49 patients were identified in case reports and were treated with rFVIIa for 36 bleeding episodes and 29 surgical procedures . Patients ranged in age from 1 to 60 years; 53% were female and 47% were male (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, 49 patients were identified in case reports and were treated with rFVIIa for 36 bleeding episodes and 29 surgical procedures . Patients ranged in age from 1 to 60 years; 53% were female and 47% were male (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…In all, 40 case reports were identified that included 49 patients in whom rFVIIa was used as part of their treatment regimen; in six case reports, the same patient was treated for bleeding episodes and surgical procedures. Twenty‐four case reports described 29 patients treated for 36 bleeding episodes, and 22 case reports described 27 patients treated for 29 invasive, surgical or dental procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Bakdash et al (5) could not control the bleeding in a 48-year-old female patient with endoscopic intervention, HLA-matched platelet transfusions and rFVIIa, and reported controlling the bleeding with partial gastrectomy after platelet transfusions and rFVIIa support. Bhat et al (6) used rFVIIa in their patient with GT when the patient was 4-years-old for an upper gastrointestinal system bleed, and when the patient was 9-years-old for a lower GI system bleed; they reported improvement in bleeding in their study following their experience with rFVIIa in life-threatening bleeds.…”
Section: Discussionmentioning
confidence: 99%
“…Differentiating shock because of hemoconcentration and hemorrhagic shock is critical as the management is fundamentally different. Where bleeding remains uncontrolled, activated recombinant factor VII has been used with success [ 133 , 134 ].…”
Section: Systems-based Managementmentioning
confidence: 99%